Carla carissima: Briefe, Tagebücher, Notizen - Henius, Carla; Nono, Luigi 1924-1990; Stenzl, Jürg (Hamburg Europäische Verlagsanstalt, 1995)
With the premiere of "Intolleranza" in 1961 at the Teatro La Fenice in Venice, and with the recordings of "Fabbrica Illuminata" in 1964, Nono and Henius made music history and set standards, and not just for these pieces.The volume provides insights into the working methods of one of today's most important composers and the working methods of a great singer. Letters and texts that allow the reader to participate directly in the creation of a work of art and that, taken as a whole, are much more: a mirror of their own time.“Such a creative, experimental collaboration between composer and performer is only conceivable with special performers, with musicians who have more than the skills that can be learned in the very best conservatory. Carla Henius and her life's work stand for exactly that - and Luigi Nono knew that very well." Jürg Stenzl
Includes bibliographical references (p. 125) and discography (p. 124).
Carla Henius und Luigi Nono ; mit einem Vorwort von Carla Henius und mit einem Essay und Materialien von Jürg Stenzl
Keywords: Music history; Correspondence; Singer; Composer; Italy